Next‐generation sequencing adds value to the preoperative diagnosis of pancreatic cysts. Issue 1 (20th September 2016) - Rosenbaum, Matthew W.; Jones, Martin; Dudley, Jonathan C.; Le, Long P.; Iafrate, A. John; Pitman, Martha B.
Abstract : BACKGROUND: The diagnosis of a pancreatic cyst as mucinous or high‐risk dictates the need for follow‐up or surgery. Molecular analysis of aspirated pancreatic cyst fluid (PCF) can provide valuable information not obtained by carcinoembryonic antigen (CEA) analysis or cytology. METHODS: All patients who underwent molecular analysis of PCF between March 2013 and June 2015 were reviewed, including pathology, imaging, and follow‐up. Molecular testing was performed using a patented, anchored multiplex polymerase chain reaction next‐generation sequencing (NGS) platform, which sequenced numerous hotspots in 39 genes linked with malignancy. Performance of NGS and cytology was calculated using final outcome, as determined by clinicopathologic follow‐up. RESULTS: The study cohort included 113 PCFs from 105 patients. In total, 119 variants were detected in 67 PCFs (59%). Variants were more common in intraductal papillary mucinous neoplasms (IPMNs)/cancer than in nonmucinous cysts ( P  < .005). The inclusion of v‐Ki‐ras2 Kirsten rat sarcoma viral oncogene homolog ( KRAS )/guanine nucleotide‐binding protein ( GNAS ) variants improved the classification of IPMNs as mucinous from 50% by microscopy to 100%. Seventy‐five percent of cancers had high‐grade atypia versus 0% of IPMNs and nonmucinous cysts ( P  < .002). Variants in tumor protein 53 ( TP53 ), SMAD family member 4 ( SMAD4 ), cyclin‐dependent kinase inhibitor 2A ( CDKN2A ), and notch1 ( NOTCH1 ) were detected only in malignant cysts. Cytology was similarly specific (100%) for detecting malignant cysts but was more sensitive than the identification of late mutations by NGS (75% vs 46%). CONCLUSIONS: The detection of KRAS / GNAS variants improves the identification of mucinous neoplasms. Variants in TP53, SMAD4, CDKN2A, and NOTCH1 support the diagnosis of a high‐risk cyst requiring surgery or additional sampling. Although molecular analysis is not a replacement for cytopathology, it does provide valuable information for accurate preoperative diagnosis, helping to classify mucinous neoplasms and high‐risk cysts that require surgical resection. Cancer Cytopathol 2017;125:41‐47 . © 2016 American Cancer Society . Abstract : Next‐generation sequencing is a useful adjunct to preoperative cytologic diagnosis of pancreatic cysts sampled by endoscopic ultrasound‐guided fine‐needle aspiration. The detection of KRAS and/or GNAS variants supports a mucinous etiology; whereas the detection of variants in TP53, SMAD4, CDKN2A, and NOTCH1 supports a high‐risk cyst requiring resection.